Extreme resistance to Potato virus Y in potato carrying the Rysto gene is mediated by a TIR‐NLR immune receptor. Issue 3 (4th September 2019) - Grech‐Baran, Marta; Witek, Kamil; Szajko, Katarzyna; Witek, Agnieszka I.; Morgiewicz, Karolina; Wasilewicz‐Flis, Iwona; Jakuczun, Henryka; Marczewski, Waldemar; Jones, Jonathan D. G.; Hennig, Jacek
Summary: Potato virus Y (PVY) is a major potato ( Solanum tuberosum L.) pathogen that causes severe annual crop losses worth billions of dollars worldwide. PVY is transmitted by aphids, and successful control of virus transmission requires the extensive use of environmentally damaging insecticides to reduce vector populations. Ry sto, from the wild relative S. stoloniferum, confers extreme resistance (ER) to PVY and related viruses and is a valuable trait that is widely employed in potato resistance breeding programmes. Ry sto was previously mapped to a region of potato chromosome XII, but the specific gene has not been identified to date. In this study, we isolated Ry sto using resistance gene enrichment sequencing (RenSeq) and PacBio SMRT (Pacific Biosciences single‐molecule real‐time sequencing). Ry sto was found to encode a nucleotide‐binding leucine‐rich repeat (NLR) protein with an N‐terminal TIR domain and was sufficient for PVY perception and ER in transgenic potato plants. Ry sto ‐dependent extreme resistance was temperature‐independent and requires EDS1 and NRG1 proteins. Ry sto may prove valuable for creating PVY‐resistant cultivars of potato and other Solanaceae crops.